2021
DOI: 10.3390/medicina57010052
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Endurance and Ultra-Endurance Running

Abstract: Background and objectives: The COVID-19 outbreak has become a major health and economic crisis. The World Health Organization declared it a pandemic in March 2020, and many sporting events were canceled. Materials and Methods: We examined the effects of the COVID-19 pandemic on endurance and ultra-endurance running (UER) and analyzed finishes and events during the COVID-19 pandemic (observation period March 2020–October 2020) to the same time period pre-COVID-19 outbreak (March 2019–October 2019). Results: End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…As reported by Scheer, the events that limited by distance and time was significantly decreased during this pandemic, and they suggested that it was impossible that running events could return to pre-pandemic levels soon (33). Negative influence on running tests was observed on male 50-m dash and 1,000-m/800-m race in our study as well.…”
Section: Discussionsupporting
confidence: 78%
“…As reported by Scheer, the events that limited by distance and time was significantly decreased during this pandemic, and they suggested that it was impossible that running events could return to pre-pandemic levels soon (33). Negative influence on running tests was observed on male 50-m dash and 1,000-m/800-m race in our study as well.…”
Section: Discussionsupporting
confidence: 78%
“…The popularity of UER has increased over the last 2 decades [ 2 ] and, in 2019 alone, over 669,000 runners contested more than 7000 UER events around the world [ 3 ]. Participation in UER decreased significantly in 2020 due to the worldwide coronavirus disease 2019 (COVID-19) pandemic [ 4 ]. To date, research in UER has focused predominantly on acute injuries and medical problems, as well as physiological, biochemical, nutritional, performance, and training-related aspects [ 5 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019 alone, over 669,000 runners finished an UER event and there were over 7000 UER events hosted around the world (DUV, 2019). The exception of course, was 2020, with a significant reduction in UER participation and events, due to the global COVID-19 pandemic (Scheer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%